Problematika Pernikahan Dini Terhadap Kesejahteraan Ekonomi Keluarga Dalam Perspektif Ekonomi Syariah - layyinah, Khoiriyatul; Sunariyah, Anik; Hipni, Mohammad; Mawardi, Imam (USRAH: Jurnal Hukum Keluarga Islam, 2024)
Early marriage is a marriage under age, where there is no mature readiness to carry out married life. Teenagers will experience difficulties because the reason they are getting married is not because they are ready so that early marriage can occur for various reasons. Marriage is a highly valued institution, where family economic stability is one of the main goals. However, when marriage is carried out at a too young age, the couple is often not ready physically and mentally. Therefore, the aim of this research is to analyze the problems that occur in families who engage in early marriage in the community in Burneh District and their relationship to the family's economic welfare from a sharia perspective. This research was conducted using descriptive qualitative methods, the data collection techniques used were observation, interviews and documentation related to the problems of early marriage. The research results show that early marriage has a negative impact on the family's economic well-being, causing an inability to manage the family economy effectively, thereby triggering dependence on debt and a lack of long-term savings. From a sharia economic perspective, this problem is contrary to the principles of justice in the distribution of wealth and the obligation to fulfill basic needs within the family. Keywords: Early-age marriage; Economic Welfare; Family.